Information rules : a strategic guide to the network economy - Shapiro, Carl; Varian, Hal R. (Boston, Mass. : Harvard Business Press, 1999)
Annotation As one of the first books to distill the economics of information and networks into practical business strategies, this is a guide to the winning moves that can help business leaders--from writers, lawyers and finance professional to executives in the entertainment, publishing and hardware and software industries-- navigate successfully through the information economy.
Annotation.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 16, 2018).
Added to collection customer.56279.3
Keywords: Information technology -- Economic aspects; Information society; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Information society; Information technology -- Economic aspects; elektronické knihy; electronic books